Didactics of Piety in Children's Edifying Literature in the Early 18th Century - Schmid, Pia (Zutot, 2019)
This article focuses on an aspect of Pietist education that may be regarded as a reform, namely a new way of upholding the role model to educational ends - or, more simply put, of teaching by example. This new approach to the example, according to my thesis, manifests itself in an implicit, narrative didactics of piety. This will be illustrated by reference to a popular genre of children' and young people's literature dating from the 17th and 18th centuries, namely exemplary children's stories' (Kinderexempelgeschichten). Such stories consist of biographical model narratives concerning exemplary pious boys and girls. To demonstrate how this implicit, religious didactic was made explicit, I draw on the text Christliche Lebens=Regeln' (Christian Rules of Life), which was especifically conceived as a systematic elucidation of exemplary stories.